The Pengembangan Ensiklopedia Terintegrasi STEM (Science, Technology, Engineering, Mathematics) Sebagai Pengayaan Bagi Peserta Didik Di Sekolah Dasar: Pengembangan Ensiklopedia Terintegrasi STEM (Science, Technology, Engineering, Mathematics) Sebagai Pengayaan Bagi Peserta Didik Di Sekolah Dasar - Vera Yuli Erviana (Jurnal Inovasi Pendidikan Dasar, 2019)
This study aims to develop an integrated thematic learning encyclopedia media STEM that can help increase understanding of the material and improve critical and creative thinking skills in students. This type of research is Research and Development (RnD) using ADDIE research design. The experimental subjects used in this study were grade 3 students of Muhammadiyah Ambarbinangun Elementary School, totaling 49 children. Data collection techniques are interviews, questionnaires, and tests. Data collection instruments are encyclopedia assessment sheets, test results, and interviews. Data analysis techniques are qualitative and quantitative data. The results showed that the average of expert validation test assessments were 86.35 with "very good" categories, the average of teacher ratings was 96.66 with "very good" categories, and the average rating of students was 91 , 59 with the category "very good". From these results, the encyclopedia media is declared "feasible" to be used in learning. In addition, the study showed that the effective encyclopedia was used in learning based on calculations using the Paired Sample T-Test. The results obtained were Tcount 12.064 and Ttable 2.056 with a significance of 0.000 <0.05, meaning that there were significant differences between the results of theassessments pretest and posttest.